Peningkatan Hasil Belajar Peserta Didik Menggunakan Model Problem Based Learning pada Materi Ciri-Ciri Bangun Datar di Kelas IV SDN 10 Koto Baru Kabupaten Solok - Fitri, Nadya Adila; Ariani, Yetti; Suciana, Fadila; Masniladevi, Masniladevi (Lembaga Intelektual Muda (LIM) Maluku, 2025)
This study aims to describe the improvement of student learning outcomes using the Problem Based Learning model on the material Characteristics of Flat Shapes in class IV SDN 10 Koto Baru, Solok Regency. This study is a Classroom Action Research (CAR) using qualitative and quantitative approaches which is carried out in two cycles. Each cycle consists of planning, implementation, observation and reflection. The subjects in this study were teachers and students of class IV SDN 10 Koto Baru totaling 18 people in the January-June semester of the 2024/2025 academic year. The research data are in the form of observations of teaching modules, teacher and student activities, and student learning outcomes using the Problem Based Learning model. Data collection techniques are in the form of observation analysis, tests and non-tests. The results of the assessment of the teaching module in cycle I obtained an average of 87.5% (B) increasing in cycle II to 95.83% (SB). The results of the implementation of learning aspects of teachers in cycle I obtained an average of 87.5% (B), increasing in cycle II to 96.42% (SB). The results of the implementation of learning aspects of students in cycle I obtained an average of 87.5% (B), increasing in cycle II to 96.42% (SB). The learning outcomes of students in cycle I obtained an average of 74.31 (C), increasing in cycle II to 85.05 (B). Thus, it can be concluded that the Problem Based Learning Model can improve student learning outcomes in learning Characteristics of Flat Shapes in class IV SDN 10 Koto Baru, Solok Regency.